The Limitation of Pre-processing Techniques to Enhance the Face Recognition System Based on LBP - Muhammad , Raafat Salih; Younis , Mohammed Issam (Iraqi Journal of Science, 2022)
Most systems are intelligent and the industrial world is moving now towardstechnology. Most industrial systems are now computerized and offer a high speed.However, Face recognition is a biometric system that can identify people from theirfaces. For few number of people to be identified, it can be considered as a fastsystem. When the number of people grew to be bigger, the system cannot be adoptedin a real-time application because its speed will degrade along with its accuracy.However, the accuracy can be enhanced using pre-processing techniques but thetime delay is still a challenge. A series of experiments had been done on AT&TORLdatabase images using Enhanced Face Recognition System (EFRS) that isadopting a Local Binary Pattern Histogram (LBPH) as feature extraction method.During these experiments, LBP parameters and pre-processing techniques have beenchanging and the results were recorded for accuracy and time for different databasesizes. The accuracy reaches 98.5% but the time delay keep increasing with thenumber of people in the database.